SEEKING FOR OPTIMISM IN â€œSANG PEMIMPIâ€ NOVEL :A CRITICAL BOOK REVIEW - Chairunnisa, Suci; Sari, Risma; Gultom, Kristina (Lisan: Jurnal Bahasa dan Linguistik, 2019)
Novel Sang Pemimpi (NSP) is the second novel written by Andrea Hirata from the Laskar Pelangi tetralogy. This research focuses to explore and understand the values of optimism in NSP using a psychological approach, based on 6 characteristics of optimism in Daniel Goleman book (1995) â€œEmotional Intelligence.â€Â Â The characteristics of optimism include: having high expectations, not easily discouraged, being able to motivate themselves, having high self-confidence, not being resigned, and seeing something as a thing that can be changed. This study found that all 6 characteristics of optimismÂ Â in NSPÂ Â using the content analysis method In a descriptive qualitative approach based on the principles designed by Meleong (2005), this study sees that this novel teaches the importance of having a dream and a strong effort to realize that dream even in a state of complete limitations Â 